Plenty, Portents and Plague: Ecclesiastical Readings of the Natural World in Early Medieval Europe. (4th January 2016) - Foot, Sarah
Abstract : Noli pater Father do not allow thunder and lightning, Lest we be shattered by its fear and its fire. We fear you, the terrible one, believing there is none like you. All songs praise you throughout the host of angels. Let the summits of heaven, too, praise you with roaming lightning, O most loving Jesus, O righteous King of Kings. (Thomas Owen Clancy and Gilbert Márkus, Iona: The Earliest Poetry of a Celtic Monastery, 85) Early medieval attitudes to the natural world were distinctly ambivalent. At one level the natural world represented the marvel of God's creative power; filled with beauty, it supplied everything necessary for human existence, meriting praise, as in the hymn sung by the herdsman from Whitby, Cædmon: